Penerapan Prinsip Good Governance Dalam Pengelolaan Keuangan Di Sekretariat DPRD Manado - Makalikis, Deisy Christin; Ilat, Ventje; Pusung, Rudy J. (Universitas Sam Ratulangi, 2022)
The purpose of this study is to analyze how the form of applying the principles of good governance in the principles of accountability, law enforcement, transparency and responsibility for financial management at the Manado DPRD Secretariat. The author uses a qualitative descriptive comparative method and the data obtained through documentation, observation and then documentation and interview. This research shows that the legal principles of transparency and participation have been properly applied in terms of financial management plans and responsibilities. While in the accountability of financial management. Despite the transparency principle participation and the rule of law have been implemented properly. But there are still difficulties in the administrative process. The problem is because every year there are regulations that are changed. Thereore, the Secretariat Office urgently needs the assistance of the Central Government in adjusting the changes to existing regulations.Keywords: Accountability, Transparency, Responsibility, Good Governance